2010
DOI: 10.1111/j.1748-3743.2010.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

How older people nurses assess cognitive function through daily observation

Abstract: Until a valid instrument becomes available, nursing staff must standardise daily observations themselves. This paper describes input to achieve this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…It is likely that difficulties arose because assessment of the five aspects of cognitive function depended on the clinical judgment of individual nurses and the nurses had to decide how these items should be assessed. Furthermore, assessing cognitive impairment on admission can be difficult and nurses often require several days of observation to reach a final judgment on cognitive function (Persoon, Van der Cruijsen, Schlattmann, Simmes, & Van Achterberg, ). It is important to assess cognitive impairment accurately because it is an important risk factor that caused 34% of the falls in a study by Tzeng ().…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that difficulties arose because assessment of the five aspects of cognitive function depended on the clinical judgment of individual nurses and the nurses had to decide how these items should be assessed. Furthermore, assessing cognitive impairment on admission can be difficult and nurses often require several days of observation to reach a final judgment on cognitive function (Persoon, Van der Cruijsen, Schlattmann, Simmes, & Van Achterberg, ). It is important to assess cognitive impairment accurately because it is an important risk factor that caused 34% of the falls in a study by Tzeng ().…”
Section: Discussionmentioning
confidence: 99%
“…Results from a study suggested that nurses recorded their observations of older patients’ cognitive function based on their own discretion and decided themselves what and how much to record. The nurses recorded objective observational behaviour along with their own interpretations (Persoon et al. , 2010).…”
Section: Discussionmentioning
confidence: 99%